Contemporary Design of Cultural Park in Binjai City - Nurul Hafizah Hasibuan; Mohammad Dolok Lubis (Talenta Publisher, 2023)
A cultural park is a location with both closed and open spaces where locals and visitors may create and plan events related to art and culture. Cultural parks should have the capacity to reflect local culture and promote the growth of the arts and culture in a community. However, because these activities are not seen as important, Binjai City lacks a unique location to host cultural events. One of the issues with the absence of public opinion and interest in culture and art in the City of Binjai is the lack of engaging educational and recreational cultural tourism. Because of this, the Binjai City administration needs to create a space where young people may be encouraged to develop their artistic and cultural interests and expand the city's tourism amenities. It is hoped that the cultural park building's indoor and outdoor spaces will play a significant role as a public facility based on social values in local artistic and cultural activities, become a leisurely tourist destination, and provide social education-based public services in maintaining culture in the City of Binjai. As a result, the building has a modern and current local cultural character thanks to the contemporary architectural style employed in developing this cultural park. This does not preclude the possibility of becoming one of the factors that promote the Binjai metropolis's manifestation as a vibrant metropolis for both young and old generations.